Jejunal Leiomyoma presenting as intussuception. - Paras, KP; Pankaj, KG; Ashwani, K; Parul, KG; Ashish, K; Nikhil, M (Department of Surgery, UKM Medical Centre, 2013)
Tumors of the small intestine are rare. Even though the small bowel accounts for 80% of the length and 90% of the mucosal surface of the gastrointestinal tract, only 3% to 6% of gastrointestinal tumors and 1% of gastrointestinal malignancies arise from the small bowel. Leiomyoma, adenoma, lipoma, haemangioma, fibroma and hamartoma of the small intestine are considered to be benign neoplasm. Most small bowel tumors are incidental findings at operation or autopsy. Here we present a case of benign tumour of the small intestine, histologically diagnosed as leiomyoma, presented in Surgery Emergency Ward with intestinal obstruction, treated conservatively with no improvement and hence subjected to emergency exploratory laparotomy which revealed intusussception and leading cause of which was a benign leiomyoma. The literature is revised emphasizing issues of pathophysiology, specific characteristics and the treatment of this tumour.